Innovative work behaviour in the public sector: The roles of task characteristics, social support, and proactivity. Issue 1 (26th March 2019) - Suseno, Yuliani; Standing, Craig; Gengatharen, Denise; Nguyen, Diep
Abstract: This study examines the roles of task characteristics, organisational social support, and individual proactivity on innovative work behaviour (IWB) in the public sector. Analysing empirical data from 154 employees from a government agency in Australia, we found that task characteristics, organisational social support, and proactive personality have a positive impact on IWB. Proactive personality is also found to be a moderator in the relationship between task characteristics and IWB. The findings suggest the need to design human resource practices that better identify proactive and innovative job applicants in the recruitment and selection process. Further, we highlight the requirement to organise and design work that recognises the need to develop social support to improve IWB. The implications of the study for further research on IWB are discussed.